The Role of Problem-Based Learning in Developing Critical Thinking and Improving Learning Outcomes of Fifth Grade Students - Wulandari, Tanti; Sitompul, Nurmida Catherine; Rusmawati, Retno Danu (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
21st-century learning requires students to develop critical, creative, and collaborative thinking skills, as well as the ability to solve contextual problems. However, learning practices in elementary schools are still dominated by expository strategies, which render student’s passive and discourage the development of higher-order thinking skills. Research on the application of problem-based learning strategies to improve critical thinking skills and learning outcomes, particularly in natural disasters, is still limited. This study used a quasi-experimental method with a Nonequivalent Control Group Design on 104 fifth-grade students, divided into an experimental class using problem-based learning and a control class using an expository strategy. The instruments, a learning achievement test and a critical thinking test, were tested using Cronbach’s Alpha in IBM SPSS Statistics 27, while pretest and posttest data were analyzed using an Independent Samples T-Test at a significance level of 0.05. The results showed a significant effect of problem-based learning strategies on improving learning outcomes and critical thinking skills, in line with constructivist theory, which emphasizes active student involvement. This strategy is more effective than expository learning and is recommended for wider implementation.